Age and Sex Structure of the Population of the Potapovo and Sintashta Cultures in the Late Bronze Age Based on the Materials of Funerary Monuments from the Volga-Ural Region - Artem V. Bogdanash; Еgor P. Kitov (Нижневолжский археологический вестник)
The paper analyzes the gender and age structure of the population of the Potapovo and Sintashta cultures in the late Bronze Age based on anthropological materials from a cemetery in the Volga-Ural region. According to archaeological data, both of them belong to a single cultural block; nevertheless, issues of their correlation and primacy in the time of origin are still debatable. 336 markers of gender and age definition in the individuals were applied. Calculations of the main demographic indicators were carried out; histograms of the ratio of age and gender groups were constructed for each culture under consideration. Using the principal components method, an intergroup comparison was carried out on demographic indicators of 31 series in the south of Eastern Europe and Transcaucasia. The indicators of the Potapovo and Sintashta groups have high infant mortality. At the same time, more even ratios of sex and age classes were noted for the Sintashta group of the Trans-Urals. In contrast to Potapovo, a more favorable external and internal social situation for the Sintashta population is assumed. A comparison of demographic indicators against a broader geographical and chronological background demonstrates, firstly, the convergence of the Potapovo and Sintashta groups, the manifestation of similar trends among subsequent series of log culture in the same region, and, on the contrary, sharp differences with the data of the previous pastoral Yamno-Poltavka population. Thus, the demographic indicators of the Potapovo and Sintashta cultures can symbolize the transition to new ethno-cultural living conditions, to the beginning of the formation of stationary geographical points, to the gradual settling of collectives.